Investigation of unprovoked venous thromboembolism: a case for a tempered approach?. Issue 10 (October 2016) - Hussain, T.I.; Stephenson, J.A.; Das, B.; Naqvi, S.; Verma, R.; Barnes, D.
Abstract : Aim: To investigate and review the diagnostic yield for occult malignancy in patients who underwent abdominopelvic computed tomography (CT) after the diagnosis of unprovoked venous thromboembolism (VTE) with reference to the guidelines set by The National Institute for Health and Clinical Excellence (NICE). Materials and methods: We retrospectively reviewed all unprovoked VTE diagnosed within a large teaching hospital over a period of 21 months for subsequent imaging investigations and cancer diagnoses. The primary outcome was confirmed cancer diagnosis; patients were followed for a minimum of 12 months. Results: Three hundred and five unprovoked VTEs were diagnosed in the study period, 31% of all VTEs. Of this cohort, 73.1% underwent further imaging for exclusion of occult malignancy. Fifteen (4.9%) cancers were diagnosed; with no subsequent malignancy reported in a 12-month follow-up period of the remaining 290 patients. Of the 15 cancers, seven were post-pulmonary emboli, all of which were identified on the initial CT pulmonary angiogram, thus abdominopelvic CT only was used to locate the primary and to undertake staging. Eight were post-deep-vein thrombosis (DVT). Thus the diagnostic yield for malignancy on abdominopelvic CT post-unprovoked VTE was 2.3%. The majority of diagnosed cancers were advanced with 80% dying in the follow-up period with a mean survival of 3.4 months. Conclusion: The pick-up rate of occult malignancy on abdominopelvic CT post-unprovoked VTE in the present study was 2.3%, far less than the generally quoted rate of 10%; however, similar to other rates in the literature. The benefit abdominopelvic CT brings to the diagnosis of occult malignancy post-unprovoked VTE is irresolute. Highlights: We examine the benefit of radiological investigation for occult malignancy in unprovoked VTE. Interpretation of NICE guidelines potentially leads to unnecessary radiological investigations. The benefit abdomino-pelvic CT to identify occult malignancy in these patients is limited.